Can Operating, Investment and Funding Cash Flow Increase the Stock Price of a Food and Beverage Company - Budi Wahono; Khalikussabir (Jurnal Economic Resource, 2021)
This study analyzes the effect of operating, investment, and funding cash flows on stock prices in food and beverage companies listed on the Indonesia Stock Exchange. This study involved six companies from 14 food and beverage industry companies listed on the Indonesia Stock Exchange. The sampling technique used purposive sampling, with sample criteria (e.g., the company's shares remained actively operating until December 2012; the company publishes its financial statements regularly and earns a profit every year; the company has never been delisted from the Indonesia Stock Exchange during the estimation period, and financial statements have been audited and have been submitted until December 2012). Research data in the form of quantitative and qualitative data sourced directly from the respondents' responses and related documents. Data were collected using the methods of observation, interviews, and documentation. After the data was collected, data analysis was carried out consisting of classical assumption test (normality test, heteroscedasticity test, and multicollinearity test), multiple linear regression analysis, F test, and t test. The results show that operating cash flow has a positive and significant effect on stock prices, while investment and funding cash flows have a negative and significant effect on stock prices in Food and Beverage Industry Companies listed on the Indonesia Stock Exchange.